Peningkatan Literasi Keuangan Anak Sejak Dini Pada Sekolah Paud Sempoa Mawaddah Pekanbaru Melalui Gamifikasi - Febri Delmi Yetti (BAHRI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community service activities are carried out at the Sempoa Mawaddah Pekanbaru PAUD (Early Childhood Education Programs) School. The aim of community service is to increase financial literacy from an early age in PAUD students. The method used in community service activities is the gamification method. There were thirty students and five PAUD mothers participating in community service activities. The implementation of the activity was carried out by two lecturers and four students from the Faculty of Economic and Social Science State Islamic University Sultan Syarif Kasim Riau. The gamification method explains the delivery of material, namely financial management related to learning to manage money by saving it through a simple piggy bank that is distributed to students. This gamification method will make it easier to help PAUD students and teachers to apply simple financial management, namely through a learning-whileplaying system. The result of providing this community service activity is an increase in financial literacy for PAUD students to learn to save, with an accuracy of 71% before Abdimas to 96% afterward. Through the gamification method, PAUD teachers obtain new information in the form of ways in the financial learning system while playing which increases financial literacy from 87% to 93% after community service, besides that, it can also help PAUD parents to participate in providing financial understanding in families who become it's easier when the piggy bank is brought home and reviewed again in class during the implementation of community service activities. The increase in the financial literacy of parents PAUD students from before community service activities was 71%, to 96% after joint discussions regarding financial literacy skills.